The preventive effect of the combination of atorvastatin and nortriptyline in migraine-type headache: a randomized, triple-blind, placebo-controlled trial. (3rd April 2022) - Sherafat, Amir; Sahebnasagh, Adeleh; Rahmany, Roya; Mohammadi, Farhad; Saghafi, Fatemeh
ABSTRACT: Background and purpose: Migraine ranked as the eighth cause of disability worldwide. Statins with anti-inflammatory and vasodilatory endothelial effects have been introduced as an option for the prevention of migraine-type headaches. The current study aimed to assess the efficacy and tolerability of atorvastatin for the prevention of migraine in adults. Method: This prospective, triple-blind, randomized controlled clinical trial was performed in adult migraineurs from mid-July 2019 to late-April 2020. Patients were randomly assigned to receive atorvastatin or placebo in combination with nortriptyline for 24-weeks. The frequency of headache was the primary outcome, and intensity of the headache and quality of life (QOL) were the secondary outcomes for this study. Results: With 34 patients in each arm, 68 patients with migraines based on the International Headache Society (IHS) criteria were enrolled in the study. At week 24, patients in the atorvastatin group experienced significantly fewer migraine attacks than the placebo group (P-value = 0.004). Moreover, there were significant differences between the two groups in QOL at follow-up intervals of 14 (P-value = 0.001) and 24 (P-value < 0.001) weeks. However, no significant difference was observed in the intensity of headache was observed in both groups (P-value > 0.05). The most common adverse effects in intervention and control groups were constipation and insomnia, respectively. Conclusion: In patients with migraine, prophylaxis with atorvastatin significantly improved the frequency of headache and QOL over 24 weeks compared with placebo with no effect on the intensity of headache. Statins seem to be a potential promising drug for prophylaxis of migraine headaches.